(untitled) (Journal of Mining and Metallurgy, Section B: Metallurgy, 2016)
This work examines the role of NaOH and Ca(OH)2 on the hydrothermal decomposition of industrial jarosite deposited by a Mexican company in a tailings dam. The industrial jarosite in mainly composed by natrojarosite and contains 150 g Ag/t, showing a narrow particle size distribution, as reveled by XRD, fire assay, SEM-EDS and laser-diffraction analysis. The effect of the pH, when using NaOH or Ca(OH)2 as alkalinizing agent was studied by carrying out decomposition experiments at different pH values and 60°C in a homogeneous size particle system (pH = 8, 9, 10 and 11) and in a heterogeneous size particle system (pH = 11). Also, the kinetic study of the process and the controlling step of the decomposition reaction when NaOH and Ca(OH)2 are used was determined by fitting the data obtained to the shrinking core model for spherical particles of constant size. These results, supported by chemical (EDS), morphological (SEM) and mapping of elements (EDS) analysis of a partially reacted jarosite particle allowed to conclude that when NaOH is used, the process kinetics is controlled by the chemical reaction and when Ca(OH)2 is used, the rate determining step is changed to a diffusion control through a layer of solid products.